Determinants of venture capital fundraising – example of Germany - Milica Šušljik; Vera Mirović; Nada Milenković; Snježana Zarić (Anali Ekonomskog fakulteta u Subotici, 2025)
Abstract Purpose: Venture capital is essential for developed markets as they provide possible start-ups with capital, especially the ones which have great prospects of success and growth. There are a few factors which influence the venture capital. Therefore, the study aims to investigate which factors affect significantly venture capital fundraising in Germany.Methodology: This research is conducted by using a log-lin regression model which covers the data from 2015 to 2024 in Germany. The dependent variable is the amount of venture capital fundraising, whereas independent determinants are unemployment rate, global innovation index, price-to-book ratio, corporate tax rate and industrial index.Findings: The results show that unemployment rate, global innovation index and corporate tax rate have a significant effect on the dependent variable. However, price-to-book ratio and industrial index have no significance on venture capital fundraising. As a result, venture capital in Germany is mostly influenced by macroeconomic environment.Originality/value: The results show which macroeconomic determinants impact most the fundraising of the venture capital funds in Germany in this way allows the policy makers to improve the environment for the growth of the venture capital activity. Furthermore, this research, in comparison with the results of other studies, indicates that there are differences in the impact between developed countries as well. The findings of this research, especially associated with the effects of the impact of the innovation index are valuable and indicate that investors are not inclined to invest in radical innovations that are associated with high risks and therefore a high possibility of failure.Practical implications: The results can be used by policymakers and venture capital fund managers in order to attract investors to raise funds for venture capital investments.Limitations: One of the limitations is the fact that study covers the period from 2015 to 2024. Also, the results of the research cannot be applied to emerging countries.